A Framework Of Green Insurance To Safeguard Green Certified Commercial Buildings In Malaysia - Ou, Yang Yu Xin (2018)
In 2009, Malaysia adopted Green Building Index (GBI) to provide green certification to buildings that fulfil the sustainable requirements. This research is focused on newly built Green Certified Commercial Buildings (GCCB) because the value of the property will appreciate, and it is easier to maintain the certification than residential property because unlike residential property, an individual owned property, GCCB is a shared property handled by a building management team. In addition, the reputation of having a green certification to embrace its market value is essential for a GCCB for business opportunity purpose. Although the number of GCCB is increasing, yet their insurance coverage remains as conventional property insurance, which does not provide the real coverage on the status of the GCCB. Therefore, this study aims to identify the factors that could potentially drive Green Insurance into Malaysia; the strategies to promote Green Insurance effectively in Malaysia and to propose a framework for implementation of Green Insurance. Qualitative research method was used in this research and the research design is exploratory, since the novelty of the research and Malaysia still does not have green insurance for the GCCB. Moreover, the qualitative data is collected from the interview sessions with green building management team and top management from insurance companies. This research provides the insights of the possible factors, suggested strategies to promote Green Insurance effectively and proposed a new framework for implementation of Green Insurance for GCCB in Malaysia. Based on the findings, the factors and strategies have been arranged according to their significant level. The top three most significant factors to drive implementation of Green Insurance are insufficient coverage of standard commercial property insurance, increase value of GCCB and reduce climate change that can reduce catastrophe lost. In addition, based on the findings, it can be concluded that the top three significant strategies to promote Green Insurance effectively are organize community and stakeholder discussions, train the participants in workshops and forming strategic alliances between government, civil society and commercial organizations. Thus, a new framework is proposed based on the significant level of the factors and strategies for implementation of Green Insurance to GCCB. This research has identified that insurance companies and GCCB have the relationship and efforts must be done on both side to raise the awareness of Green Insurance to make it become possible. This research is important because it is time for insurance companies start to consider these GCCB to provide sufficient coverage for them as a new business opportunity. In addition, GCCB also can seek this as an opportunity to have complete risk transfer to insurance companies to safeguard their property value. Currently the insurance companies still not yet ready to provide Green Insurance for GCCB because GCCB still relative new in the market. Therefore, the lack of claim history causes insurance companies still required some time to observe this potential market.